(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Diabetic foot ulcers are a major source of concern for diabetic patients due to their severity and inability to heal.70% of diabetic foot ulcers remain unhealed after 20 weeks of treatment, 60% of them become infected, and of these, 20% end in different levels of amputation. The present study was intended to assess the role of the SINBAD scoring system in predicting the risk of amputation in diabetic foot patients. METHODOLOGY It is a prospective study conducted in MEENAKSHI MEDICAL COLLEGE HOSPITAL AND RESEARCH INSTITUTE for a duration of 2 the years 2020 to 2022, with the source of study being, a total of 150 patients admitted to the general surgery ward with diabetic foot ulcers presented during the study period. According to the SINBAD classification system scoring, diabetic foot ulcers were done. RESULTS Most of the patients were males (65.3%) and the male-female ratio was 1.8:1in this study. The mean age is noted as 60 years and in females, the mean age is 55.3 years. In this study, the size of the ulcer was greater than 1cm in the majority of patients (92.66%). Most ulcers were superficial (82%) and were present on the forefoot. Most of the patients had a SINBAD score of 2 (74.67%) and all the patients with a SINBAD score of 2 recovered by healing without amputation. In this study patients with a SINBAD score greater than 3 had a 100% risk of amputation. CONCLUSION The outcome and the risk of amputation in diabetic foot ulcer patients, increase with the increasing scores on SINBAD scoring system.